Shaping Students' Islamic Character: The Role of Teachers in Practicing Religious Values - Rayyan Dina Amaliya; Juliani; Rizky Alfi Syahrin; Sinta Nur Hilalyah; Rahma Dhini Zulham Putri Siregar (Yayasan Zia Salsabila, 2024)
The research that we do is very much describing the strategies faced by Islamic religious education teachers in internalizing the values of Islamic religious education to students at school. strategies that arise due to rapid developments in the field of information and technology (IT) so that the reverse flow of information exchange becomes inevitable, even many cultures that must be filtered first because they are not in accordance with the values of Islamic education. This paper also describes how the teacher's strategy in internalizing the values of Islamic religious education to students. There are three aspects included in the values of Islamic education, namely: moral values (morals to God, morals to others and morals to oneself), the value of belief (faith in God and His messenger), and the value of worship (ghairu mahdah). The strategies carried out in internalizing the values of Islamic religious education include several stages, namely the value transformation stage, the value transaction stage, and the internalization stage.